Group traits moderate the relationship between individual social traits and fitness in gorillas - Robin E. Morrison; Samuel Ellis; Victoire Martignac; Tara S. Stoinski; Winnie Eckardt (Proceedings of the National Academy of Sciences, 2025)
Evidence across a broad range of disciplines has demonstrated how individuals’ social environments can impact their health, lifespan, reproduction, and ultimately their evolutionary fitness. Past research has primarily focused on either traits specific to individuals or wider traits of social groups, linking these with a component of fitness. In this study, we examined how both individual- and group-level social traits in 164 wild mountain gorillas combine to influence multiple pathways impacting fitness over 21 y. First, we highlight key sex differences in the costs and benefits of social bonds, with strong and stable social bonds linked with lower risk of illness in females, but higher risk of illness in males. Second, we demonstrate important trade-offs in the fitness consequences of sociality, with strong and stable bonds in males linked with decreases in injury but increases in illness. Finally, we show the extensive moderating effects of group-level traits on the fitness consequences of individual-level social traits. For example, in small groups, females with strong bonds benefitted from lower rates of illness, but also showed lower birth rates, while in large groups, females with strong bonds experienced higher rates of illness but also higher birth rates. These findings highlight the complexity of selection acting on social traits, where the fitness consequences of individual’s social phenotypes are highly context dependent. We argue that this variability in the fitness benefits of sociality has likely played a fundamental role in maintaining the wide diversity of social phenotypes observed within species.